Personnel risk assesment. The case of a German start-up company - Prończuk, Anna (Zarządzanie ryzykiem personalnym. Studium przypadku niemieckiego start-upu, 2018)
The main goal of this article is to understand possible simplistic methods of assessing personnel risk at start-up companies. The author aims to prove the hypothesis that small and medium sized companies do not require sophisticated personnel risk assessment tools in order to mitigate their personnel risk. Thus, this article aims to understand strategies and KPIs that can be implemented in order to address potential stuffing problems without the need of hiring additional experts specialized in big data analysis methods. The author analyses theoretical approaches towards HR planning and aims to suggest strategies that can be implemented by middle-sized companies for their planning purposes. This paper describes a case study of a German IT start-up and its workforce planning strategy. The article presents ways for planning, implementing, and controlling workforce‒planning solutions at companies with flat and not well-established structures that need effective and efficient solutions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 506, s. 113-123
Keywords: zarządzanie zasobami ludzkimi; personnel risk management; HR controlling; HR management; workforce planning; human resources planning; zarządzanie ryzykiem personalnym; controlling personalny; planowanie zatrudnienia; planowanie zasobów ludzkich